Periodontitis is associated with incidental valvular heart disease: A nationwide population‐based cohort study - Sia, Sung‐Kien; Jan, Ming‐Shiou; Wang, Yu‐Hsun; Huang, Yu‐Feng; Wei, James Cheng‐Chung (Journal of clinical periodontology, 2021)
Aim Periodontitis and valvular heart disease (VHD) are common diseases. Both diseases are related to chronic inflammation and share many common risk factors. Previous periodontal studies had focused mainly on atherosclerotic cardiovascular disease. This study aimed to determine whether periodontitis is associated with the development of VHD. Materials and methods This was a retrospective nationwide cohort study using Taiwan's Longitudinal Health Insurance Database. Using ICD‐9‐CM coding, both the periodontitis and non‐periodontitis groups were matched. Results There were 8483 cases and 4919 cases of VHD diagnosed in the periodontitis group and non‐periodontitis group, respectively. The cumulative incidence of VHD was significantly higher in the periodontitis group (log‐rank test, p < .001), with the incidence density of 6.44 (95% CI, 6.31–6.58) per 1000 person‐years in the periodontitis group compared to 4.65 (95% CI, 4.52–4.78) in the non‐periodontitis group. The relative risk for VHD was 1.39 (95% CI, 1.34–1.44). After multivariate analysis, periodontitis was independently associated with a risk for VHD (HR, 1.38; 95% CI, 1.33–1.42, p < .001). Intensive treatment of periodontitis significantly lowered the risk for VHD (HR, 0.68; 95% CI, 0.60–0.77, p < .001). Conclusions Periodontitis was significantly associated with the development of VHD. Treatment of periodontitis reduced the risk for VHD.